2016
DOI: 10.1016/s2214-109x(16)30130-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of a screen-and-treat programme for hepatitis B virus infection in The Gambia: the Prevention of Liver Fibrosis and Cancer in Africa (PROLIFICA) study

Abstract: European Commission (FP7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
200
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(227 citation statements)
references
References 29 publications
23
200
2
2
Order By: Relevance
“…A recent review article reported HIV/HBV co-infection in the range 5.0–8.3% in East Africa and 2.7–35.7% in West Africa [29]. However, the only previous study to report HIV/HBV co-infection in an African HBV cohort found a relatively low prevalence of HIV (3.3%) among HBsAg positive individuals in The Gambia [30], in keeping with our findings. Although HIV and HBV share the same transmission routes, most adults with CHB have been infected in early childhood and would not have any increased risk of acquiring HIV later in life [31].…”
Section: Discussionsupporting
confidence: 90%
“…A recent review article reported HIV/HBV co-infection in the range 5.0–8.3% in East Africa and 2.7–35.7% in West Africa [29]. However, the only previous study to report HIV/HBV co-infection in an African HBV cohort found a relatively low prevalence of HIV (3.3%) among HBsAg positive individuals in The Gambia [30], in keeping with our findings. Although HIV and HBV share the same transmission routes, most adults with CHB have been infected in early childhood and would not have any increased risk of acquiring HIV later in life [31].…”
Section: Discussionsupporting
confidence: 90%
“…The [29]. However, the only previous study to report HIV/HBV co-infection in an African HBV cohort found a relatively low prevalence of HIV (3.3%) among HBsAg positive individuals in The Gambia [30], in keeping with our findings. Although HIV and HBV share the same transmission routes, most adults with CHB have been infected in early childhood and would not have any increased risk of acquiring HIV later in life [31].…”
Section: Discussionsupporting
confidence: 91%
“…Two factors were significantly associated with HbsAg: gender and ever having sexual intercourse. The Gambia, a prevalence of 3.1% was found among male blood donors between the ages of 16 and 19 [19]. In addition, the data from the PROLIFICA study indicates that the prevalence of HBsAg positivity increased with age among men from the blood bank and men from the community to reach a peak between 30…”
Section: Discussionmentioning
confidence: 97%